A Single‐Cell Assay for Time Lapse Studies of Exosome Secretion and Cell Behaviors. Issue 27 (2nd June 2016) - Chiu, Yu‐Jui; Cai, Wei; Shih, Yu‐Ru V.; Lian, Ian; Lo, Yu‐Hwa
Abstract : To understand the inhomogeneity of cells in biological systems, there is a growing demand on the capability of characterizing the properties of individual single cells. Since single‐cell studies require continuous monitoring of the cell behaviors, an effective single‐cell assay that can support time lapsed studies in a high throughput manner is desired. Most currently available single‐cell technologies cannot provide proper environments to sustain cell growth and, proliferation of single cells and convenient, noninvasive tests of single‐cell behaviors from molecular markers. Here, a highly versatile single‐cell assay is presented that can accommodate different cellular types, enable easy and efficient single‐cell loading and culturing, and be suitable for the study of effects of in vitro environmental factors in combination with drug screening. One salient feature of the assay is the noninvasive collection and surveying of single‐cell secretions at different time points, producing unprecedented insight of single‐cell behaviors based on the biomarker signals from individual cells under given perturbations. Above all, the acquired information is quantitative, for example, measured by the number of exosomes each single‐cell secretes for a given time period. Therefore, our single‐cell assay provides a convenient, low‐cost, and enabling tool for quantitative, time lapsed studies of single‐cell properties. Abstract : A convenient and low‐cost single‐cell assay is developed to accommodate different cellular types, enable easy and efficient single‐cell loading and culturing, and be suitable for the time lapse study of effects of drugs and in‐vitro environmental factors. Quantitative biomarker signals such as the amount of exosomes secreted by each single cell over a given time period have been measured in a noninvasive manner.